Fertility decision making: to what extent do adaptations, social pressures, and individual differences influence plans to have a child? - Adair, Lora E. (Kansas State University, 2013)
An evolutionary perspective suggests that changes in resource availability produce changes in fertility decisions and desires, and that these adaptive mechanisms are sensitive to sociocultural factors that act more proximally to the decision-maker. The current work systematically investigates several factors as potential predictors of fertility decisions at the level of the individual decision-maker in a three-study design, adding to an existing literature of fertility decision-making that has focused on demographic-level shifts. In study 1 (N=228, 69.3% female, average age=25.6), study 2 (N=232, 72.4% female, average age=24.7), and study 3 (N=333, 67% female, average age=25.1) data was collected from a general Internet sample and a student sample. Findings suggest that high resource variability produces insecure romantic attachment, which is associated with increased fertility plans and desires. Further, this work indicates that fertility decision making mechanisms are sensitive to sociocultural factors, particularly gender roles and identities, cultural pressures to become a parent, mothering expectations, and relationship status. These findings suggest that demographic-level changes in fertility can be understood, with strong predictive models, at the individual-level of analysis.
Keywords: Fertility; Decision making; Sexual behavior; Evolutionary psychology; Psychology (0621)